An institutional economic appraisal of worker equity schemes in agriculture - Karaan, A.S. Mohammad (International Food Policy Research Institute, 2009)
The importance of institutional innovation as a key determinant of economic growth has received much attention in the economic literature. Joseph Schumpeter in particular was concerned with this issue and the important role of the entrepreneur whose innovations advance growth (Demsetz 2000). Lewis (1955) later gave further attention to the institutional factors in society that determine economic performance, such as property rights, population, and capital. Hayami and Ruttan (1985) later introduced the concept of induced innovations: institutional changes tend to follow price signals. More recent work relates to the innovations occurring in firms and industries that enhance global competitiveness (Best 1990; Porter 1990).